Pengembangan Model Bisnis pada Lokawisata Baturaden Menggunakan Business Model Canvas - Azhar, Ratih Mukti; Suparno, Ono; Djohar, Setiadi (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2017)
The development of tourism sector in this era of globalization requires each business actor in this sector to continue development business including Lokawisata Baturaden which is one of the natural tourist attractions located in Central Java. Therefore, it is necessary to design the right business model so that Lokawisata Baturaden can understand how to run management activities effectively and efficiently. The objective of this study was to design a future business model of Lokawisata Baturaden as a developed tourism recreation. The analytical method utilized in the study was business model canvas (BMC) with SWOT and blue ocean strategy. The results showed that created of new value proposition for future business model design in the form of educational entertainment programs for children and families in Lokawisata Baturaden affected  every element of the business model canvas such as the addition in terms of key resources owned, key activities undertaken, cooperation partners, and income streams who signed in. The cost structure incurred addition and reduction of costs in terms of promotional activities. Costumer segment, the main focus is family, children, and students.